Time and State Legislation Have Decreased Opioid Prescribing in Elective Foot and Ankle Surgery in the United States - Daniel J. Cunningham MD; Nicholas Kwon; Nicholas B. Allen; Andrew Hanselman; Samuel B. Adams MD (Foot & Ankle Orthopaedics, 2022)
Category: Other; Ankle; Ankle Arthritis; Arthroscopy; Bunion; Hindfoot; Lesser Toes; Midfoot/Forefoot; Sports Introduction/Purpose: The opioid epidemic has focused attention on opioid overprescribing. State legislation has been enacted to reduce acute opioid prescribing. However, the impact of this legislation on elective foot and ankle surgery is largely unknown. The purpose of this study was to evaluate the impact of opioid limiting legislation on opioid prescribing in elective foot and ankle surgery. Methods: 90-day perioperative opioid prescription filling in oxycodone 5-mg equivalents was identified in all patients ages 18 and older undergoing non-trauma, non-arthroplasty foot and ankle surgery from 2010 - 2019 using a commercial database. States with and without legislation were identified and opioid prescription filling before and after legislation was tabulated. Unadjusted and adjusted analyses were performed to evaluate the impact of time and state legislation on perioperative opioid prescribing in this patient population. Results: Initial and cumulative opioid prescribing decreased significantly from 2010 to 2019 (39 vs 35.7 initial and 98.1 vs 55.7 cumulative oxycodone 5-mg equivalents, p<0.001). States with legislation had larger and more significant reductions in initial and cumulative opioid prescribing compared to states without legislation over similar timeframes (41.6 to 35.1 with legislation vs 40.6 to 39.1 without legislation initial oxycodone 5-mg equivalents prescription filling volume and 87.7 to 62.8 vs 88.6 to 74.1 cumulative oxycodone 5-mg equivalents prescription filling volume, p<0.001). The figure shows state-level changes in opioid prescription filling from pre-act to post-act. Conclusion: State legislation and time have been associated with large, clinically relevant reductions in 90-day perioperative cumulative opioid prescription filling although reductions in initial opioid prescription filing have remained low. These results encourage states without legislation to enact restraints to reduce the impact of the opioid epidemic.